MicroRNA-125b: association with disease activity and the treatment response of patients with early rheumatoid arthritis. Issue 1 (December 2016) - Hruskova, Veronika; Jandova, Romana; Vernerova, Lucia; Mann, Herman; Pecha, Ondrej; Prajzlerova, Klara; Pavelka, Karel; Vencovsky, Jiri; Filkova, Maria; Senolt, Ladislav
Abstract Background MicroRNAs (miRNAs) are small RNAs that regulate gene expression by targeting mRNA. It was proved that some miRNAs are significantly deregulated in rheumatoid arthritis (RA). MicroRNA-125b negatively regulates expression of TNF-α, which plays a crucial role in RA pathogenesis. The aim of this study was to determine the treatment outcome of patients with early RA based on the expression of circulating and cellular miR-125b. Methods Total RNA was isolated from the plasma and peripheral blood mononuclear cells (PBMCs) of 58 patients with early RA before and three months after treatment initiation and of 54 age- and sex-matched healthy controls (HC). The expression of miR-125b was measured by TaqMan quantitative PCR. The treatment responders were defined as patients achieving remission or low disease activity (28-joint count disease activity score (DAS28) <3.2). Receiver operating characteristic (ROC) curve and stepwise backward multivariable logistic regression analyses of miR-125b expression were used to predict the disease outcome at three and six months after initiation of treatment. Results The expression of miR-125b in the PBMCs and plasma of treatment-naïve early RA patients was significantly lower than that of HC and increased significantly after three months of treatment, particularly in responders. However, only the cellular expression of miR-125b was inversely correlated with disease activity. MiR-125b expression in PBMCs was higher in responders than in non-responders after three months (p  = 0.042). Using ROC analysis, the cellular expression of miR-125b, but not the disease activity at baseline, predicted the treatment response after three months of therapy (area under the curve 0.652 (95 % CI 0.510 to 0.793);p  = 0.048). Conclusion The expression of miR-125b in PBMCs of treatment-naïve patients may present a novel biomarker for monitoring the treatment outcome during the early phase of RA.